Molecular simulation studies to reveal the binding mechanisms of shikonin derivatives inhibiting VEGFR-2 kinase. (February 2021) - Munni, Yeasmin Akter; Ali, Md. Chayan; Selsi, Nusrat Jahan; Sultana, Marium; Hossen, Md.; Bipasha, Tanjiba Harun; Rahman, Mahbubur; Uddin, Md Nazim; Hosen, S.M. Zahid; Dash, Raju
Graphical abstract: Highlights: Shikonin and β-hydroxyisovalerylshikonin bind in the allosteric site of VEGFR-2 kinase. Acetylshikonin binds in the common ATP binding region. QM/MM calculation showed that naphthazarin ring plays an important role in binding stability. Molecular dynamics simulation highlighted that the difference in side-chain of shikonin modulates binding modes of its derivatives. Abstract: Traditional vascular endothelial growth factor receptor 2 (VEGFR-2) inhibitors can manage angiogenesis; however, severe toxicity and resistance limit their long-term applications in clinical therapy. Shikonin (SHK) and its derivatives could be promising to inhibit the VEGFR-2 mediated angiogenesis, as they are reported to bind in the catalytic kinase domain with low affinity. However, the detailed molecular insights and binding dynamics of these natural inhibitors are unknown, which is crucial for potential SHK based lead design. Therefore, the present study employed molecular modeling and simulations techniques to get insight into the binding behaviors of SHK and its two derivates, β-hydroxyisovalerylshikonin (β-HIVS) and acetylshikonin (ACS). Here the intermolecular interactions between protein and ligands were studied by induced fit docking approach, which were further evaluated by treating QM/MM (quantum mechanics/molecular mechanics) and molecular dynamics (MD) simulation. The result showed that the naphthazarin ring of the SHK derivates is vital for strong binding to the catalytic domain; however, the binding stability can be modulated by the side chain modification. Because of having electrostatic potential, this ring makes essential interactions with the DFG (Asp1046 and Phe1047) motif and also allows interacting with the allosteric binding site. Taken together, the studies will advance our knowledge and scope for the development of new selective VEGFR-2 inhibitors based on SHK and its analogs.